Substrate and spatial planting pattern on the productivity of clonal mini gardens of Tectona grandis Linn. F - Rodríguez-Solís, Arantxa (2023)
Introduction. Tectona grandis is the species with the largest planted area in Costa Rica, due to the high prices in the international market. The production of plants for reforestation has been technified in the country and is currently being developed based on protected environment technologies, which increase productivity, reduce operating costs, and offer planting material throughout the year. Objective. To evaluate the effect of two substrates and five planting densities on the productivity of clonal mini-gardens of Tectona grandis in a protected environment. Materials and methods. Four readily available inert substrates were characterized by granulometry and moisture retention analysis, from which stone dust was selected as the optimum substrate. An experimental trial with a 2x5 factorial design was established in San Carlos, Costa Rica to evaluate two substrates (stone dust alone and with 25 % charcoal) and five planting densities (cm) of 10x10, 10x5, 7x5, 10x10 with two plants per hole and 10x10 with one plant in the middle. Each density had four clones as a replicate effect. The trial was evaluated during five continuous production cycles from January to September 2021. Results. The use of stone dust as substrate, without charcoal, recorded the highest productivity at a lower cost. The spatial planting arrangement of 10x10 cm with one plant in the middle (n=145 plants/m2), recorded the highest shoot production per mother plant (1.16). The 7x5 cm arrangement increased productivity by up to 206 shoots m2/month. Conclusion. The change in planting density of the clonal mini-garden, in a first stage to 10x10cm with an additional plant in the center, resulted in a high impact on productivity (74 %), greater efficiency in the use of space, and a better gradual change in the operating system.